Paraplegia due to Extramedullary Hematopoietic Tissue Compression of Thoracic Thecal Sac in a Patient with Thalassemia Treated Successfully with Surgical Decompression: A Case Report - Tiwari, Ashish; Varghese, Vineesh K.; Chand, Ashis Kumar; Chhabra, Manmeet Singh (Indian Journal of Neurosurgery, 2016)
Spinal cord compression due to extramedullary hematopoiesis (EMH) is a rare complication of thalassemia and generally presents as paraparesis with sensory impairment. Complete paraplegia is extremely rare in EMH due to thalassemia although it is known to occur in polycythemia vera and sickle cell anemia. Cases presenting with paraparesis have been treated with either surgery or radiotherapy with equal frequency and efficacy. Almost all reported cases with paraplegia have been treated with surgery with or without radiation therapy. As paraplegia secondary to EMH is rare, there is no consensus on treatment. We hereby report a case of thalassemia with paraplegia treated successfully with surgery. Treatment options for cord compression include primarily blood transfusion, surgery, and radiation therapy. Because of the extreme rarity of this condition, direct comparisons between various treatment modalities are not possible. The bias toward surgery is due to its immediate decompressing effect. EMH in thalassemia has also been treated with transfusion therapy with the rationale that correction of anemia would downregulate erythropoietin and lead to reversal of EMH. However, improvement with blood transfusion alone is usually incomplete and slow. Our patient did not improve after adequate blood transfusion and hence underwent surgical decompression after which he showed rapid and complete neurologic recovery. Therefore, we conclude that surgical decompression of EMH tissue has to be considered early in patients presenting with paraplegia if symptom shows no improvement after adequate blood transfusion.
Keywords: extramedullary hematopoietic; decompressive laminectomy; thalassemia major